INTRAOPERATIVE MITOMYCIN-C, 5-FLUOROURACIL, RETROBULBAR TRIAMCINOLON ACETONIDE, IS IT EQUALLY EFFECTIVE TO DECREASE INTRA OCULAR PRESSURE AFTER TRABECULECTOMY? - Sari, Yessi Primanda; Ekantini, Retno; Gani, Tatang Talka; Jati, Krisna Dwi Purnomo (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesTo evaluate the effect of mitomycin-C (MMC), 5-fluorouracil (5-FU), and retrobulbar triamcinoloneacetonide (TA) on the surgical result of trabeculectomy. MethodsAll consecutive trabeculectomies with releasable sutures performed in Sardjito General Hospitalbetween January 2022 and December 2022 were retrospectively reviewed from medical records.Patients without any intraoperative metabolite (control group, n=5) were compared to those withretrobulbar TA (n=5), MMC group (n=19), and 5-FU group (n=11) in terms of surgical success.Successful surgery results were defined as IOP between 5 - 21 mm Hg without any furthermedications or surgical intervention and fewer complications. Results40 eyes of 35 patients (15 male, 25 female, mean age 52.4 years) were included in the study. Patientwas observed until post-operation day (POD) 90. There were no significant differences of intraocularpressure at POD 1, 7, 30, 60, and 90 between control group compared to TCA, MMC, and 5-FUgroup. Intraocular pressure pre- and post-operation in each group was significantly different(p<0.05). The lowest mean intraocular pressure of POD 90 was in 5-FU group (13.64 ± 4.08).Complication after trabeculectomy in TCA group was 21%, MMC group was 27%, 5-FU group was10%, and control group was 42%. ConclusionMMC, 5-FU, and TCA in this study are equally effective to decrease IOP after trabeculectomy.